Hippo Pathway: An Emerging Regulator of Craniofacial and Dental Development. (October 2017) - Wang, J.; Martin, J.F.
The evolutionarily conserved Hippo signaling pathway is a vital regulator of organ size that fine-tunes cell proliferation, apoptosis, and differentiation. A number of important studies have revealed critical roles of Hippo signaling and its effectors Yap (Yes-associated protein) and Taz (transcriptional coactivator with PDZ binding motif) in tissue development, homeostasis, and regeneration, as well as in tumorigenesis. In addition, recent studies have shown evidence of crosstalk between the Hippo pathway and other key signaling pathways, such as Wnt signaling, that not only regulates developmental processes but also contributes to disease pathogenesis. In this review, we summarize the major discoveries in the field of Hippo signaling and what has been learned about its regulation and crosstalk with other signaling pathways, with a particular focus on recent findings involving the Hippo-Yap pathway in craniofacial and tooth development. New and exciting studies of the Hippo pathway are anticipated that will significantly improve our understanding of the molecular mechanisms of human craniofacial and tooth development and disease and will ultimately lead to the development of new therapies.